Threshold Analysis Of Public Cemeteries For Mapping The Suitability Of New Public Cemeteries In The Future Using Remote Sensing And Geographic Information Systems In Tasikmalaya City - Valgunadi, Ade Novit; Nandi; Annisa Joviani Astari (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2024)
The increasing population is causing changes in land use which are feared to be uncontrolled and forgetting one of the public facilities, namely cemeteries. The city of Tasikmalaya is an area that focuses on trade and services, is densely populated, and has a relatively small area so the provision of cemeteries land must be considered. This research aims to analyze the spatial distribution of cemeteries, capacity, thresholds, and suitability areas for cemeteries in Tasikmalaya City using Remote sensing methods and geographic information systems. The parameters used in in this study are; land use, slope, soil type, distance from rivers, distance from settlements, and distance from roads. The results of this research show that 1) Mapping the spatial distribution of cemeteries show that there are 101 cemeteries with an area of ±74 hectares with 3 TPUs, namely TPU Cieunteung, TPU Cinehel, and TPU Aisha Rashida. 2) Capacity and threshold if without an overlapping system, the public cemetery in Tasikmalaya City cannot accommodate the next 50 years, both with standard grave sizes and grave sizes from field surveys, whereas if once overlapping, the public cemetery in Tasikmalaya City cannot accommodate up to 50 years in the future if you use the size of the grave from a field survey and can accommodate up to 50 years in the future if you use the standard grave size. 3) The suitability of public cemeteries grounds show that Tasikmalaya City has suitable, quite suitable and unsuitable areas, each of which has an area of 2231 Ha, 14192 Ha and 1999 Ha. Suitable areas for cemeteries are concentrated in the northern part of Tasikmalaya City.